Multiwavelength Observations of Solar Magnetic Phenomena and Particle Acceleration - Clarke, Brendan Patrick (Trinity College Dublin. School of Physics. Discipline of Physics, 2022)
The solar magnetic field is instrumental in controlling the dynamics and topology of all coronal phenomena. The magnetic flux we observe varies by a factor of ~8 over a twenty-two year cycle causing a modulation in the Sun's radiation output over a broad range of wavelengths. This variation is a consequence of the evolution of the solar magnetic field from a poloidal magnetic configuration to a toroidal field produced due to the influence of differential rotation. Energetic events such as solar flares and coronal mass ejections (CMEs) are produced when this magnetic energy is released from the Sun's atmosphere in the form of thermal and kinetic energy. Modern instrumentation has allowed us to conduct detailed studies of these events. However, many questions remain unanswered. In this work, a range of phenomena associated with particle acceleration in the solar atmosphere are investigated from a multi-wavelength perspective. Firstly, an analysis of short solar radio bursts, known as S-bursts, is presented. To date, our knowledge of the solar magnetic field is only known in detail at the photosphere based on measurements of the Zeeman splitting of spectral lines. Potential field source surface (PFSS) extrapolations are typically used to estimate the coronal magnetic field. Here, we measure the properties of over 3000 S-bursts and show that S-bursts can be used to remote sense the coronal magnetic field at various altitudes. Secondly, an M-class solar flare exhibiting pronounced and broadband quasi periodic pulsations (QPPs) in its emission is investigated. QPPs have been studied for several decades, however, their origin remains unknown. Evidence is presented that the mechanism responsible for their generation is oscillatory magnetic reconnection that results in intermittent particle acceleration. This gives rise to QPPs that span in energy from the low frequency radio domain through to the high energy X-ray regime. It is shown that the source of these QPPs originates from near the energy release site of the flare. The QPPs then manifest across vast distances, from the flare footpoints through to interplanetary space. This work shines light onto the nature of energy release in flares. Finally, analysis of co-observed X-ray and radio data is presented using modern instrumentation. Combining the high cadence data available from The Spectrometer Telescope for Imaging X-rays (STIX) and I-LOFAR provides a unique opportunity to investigate the nature of high energy electrons accelerated during solar flares. It is shown that X-ray photon spectral index correlates with the beam speeds of associated type 3 radio burst sources. Software that was developed as part of this work is also presented.
APPROVED
Keywords: Solar Physics